2009
DOI: 10.1002/jrs.2445
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment and control of SERS activity of metal substrates by pressure

Abstract: Metal pellets of silver and copper for surface-enhanced Raman scattering (SERS) spectroscopy were prepared by compression with different pressures. It was found that the SERS activity of the pellet could be controlled by pressure. Enhanced Raman scattering properties of the metal pellets in the presence of adsorbed 4-mercaptobenzoic acid (4-MBA) with excitation at 632.8 or 514 nm could be obtained by choosing proper pressure of pellatization. The SERS peak intensity of the band at ∼1584 cm −1 of 4-MBA adsorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Selected peak wavenumbers for these three analytes are indicated in Figure 3. Both the overall spectral fingerprints and the peak values agree well with literature reports of SERS using these molecules [13,46,47]. Figure 4 illustrates the corresponding optical (VIS-NIR, 400-1000 nm) extinction (absorbance plus scattering) spectra.…”
Section: Resultssupporting
confidence: 84%
“…Selected peak wavenumbers for these three analytes are indicated in Figure 3. Both the overall spectral fingerprints and the peak values agree well with literature reports of SERS using these molecules [13,46,47]. Figure 4 illustrates the corresponding optical (VIS-NIR, 400-1000 nm) extinction (absorbance plus scattering) spectra.…”
Section: Resultssupporting
confidence: 84%
“…Metal pellets of silver and copper for SERS spectroscopy were prepared by Xia et al . using compression with different pressures . It was found that the SERS activity of the pellet could be controlled by pressure.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Meanwhile, s is the area occupied by a molecule of adsorbent with a monolayer coverage. According to previous reports, 46,47 the bonding density of 4-MBA molecules in a self-assembled monolayer is ca. 0.5 nmol cm À2 .…”
Section: Sers Measurementsmentioning
confidence: 82%
“…6.11 Â 10 À14 mol), which are efficiently excited by the laser beam. 47 As displayed in Fig. S2 (ESI †), the SERS intensity significantly increases after the absorption of 4-MBA on the porous Au film (curve a), compared with those on the quartz plate (curve b).…”
Section: Sers Measurementsmentioning
confidence: 92%